Quality of information and SME financial structure: Malaysian evidence - Abdul Rahman, Azhar; Masor, A. Nurhayati; Hamdan, Mohd Diah (2017)
Purpose - The objective of this study is to predict the determinants of Malaysian’s SME financial structure.We add to the literature on SME financial structure by formally testing the impact of quality of accounting information on SME financial structure, a variable which has not been explicitly tested in the Malaysian context. Previous studies were mainly conducted in developed countries.Hence, the results may not be applicable in developing country like Malaysia. Generally, capital structure of a firm may consist of equity or debt or a combination of debt and equity.Modigliani and Miller (1958) argues that, in a ‘perfect’ world, the choice between equity and debt is irrelevant.When taxes and other market imperfections are introduced, only a single optimal financial structure is available, because firms will increase debt financing until the advantage of tax deductibility of interest expenses is counterbalanced by the disadvantages of other market imperfections such as bankruptcy costs (i.e. trade-off theory-TOT).On the other hand, Pecking-order theory (POT), as proposed by Myers (1984) and Myers and Majluf (1984), is based on the assumption that inside management is better informed of the true value of the firm than outside investors.Managers will prefer those sources of funds that are less vulnerable to undervaluation resulting from information asymmetries. The theory states that firms, while making their funding choice, prefer to use internal financing (retained earnings) rather than external financing.However, if they are forced to use external funding, they prefer debt financing to equity financing.The greatest limitation of the pecking order framework is that it ignores the effects of interest tax shields, financial distress, security issuance costs, agency costs, and investment opportunities, which have been widely included in recent studies on capital structure.Whereas some studies have explicitly tried to distinguish between these theories (see e.g. Lopez-Gracia and Sogorb-Mira 2008), it appears that all the aforementioned theories help to explain SME financial structures.The results of this study show that SME leverage is positively related to asset structure, negatively related to firm size and profitability, but is not significantly related to the quality of accounting information and firm age.